Recent Developments in Control and Simulation of Permanent Magnet Synchronous Motor Systems - Azom, Md Ali; Khan, Md. Yakub Ali (Control Systems and Optimization Letters, 2025)
This paper's main goal is to present a thorough analysis of current advancements in the simulation and control of Permanent Magnet Synchronous Motor (PMSM) systems. A crucial part of contemporary electrical drive systems, the Permanent Magnet Synchronous Motor (PMSM) finds extensive use in fields like industrial automation, renewable energy systems, and electric cars. This review examines the most current developments in PMSM system control and simulation, with a focus on cutting-edge modelling techniques, new control strategies, and the most recent simulation methods. It emphasizes how increasingly complex strategies like Model Predictive Control (MPC), Sliding Mode Control (SMC), and AI-based approaches have replaced more conventional ones like PID and vector control. Advanced control techniques like Field-Oriented Control (FOC) and MPC are used by Tesla and other EV manufacturers to maximize PMSM performance, guarantee smooth torque delivery, and improve energy economy. Siemens Gamesa wind turbines use PMSMs with reliable control systems for fault tolerance and maximum energy production in a range of wind conditions. The study also discusses the developments in simulation techniques, such as the incorporation of multi-physics models, real-time simulation, and the application of AI to improve simulation efficiency and accuracy. More realistic modelling of PMSM systems in dynamic contexts is now possible thanks to recent developments in simulation approaches, such as Multiphysics models and real-time simulations. These simulations are combined with sophisticated control algorithms to give real-time input while the system is operating, which speeds up fault finding and optimization. This procedure is further improved by AI-based simulation tools, which forecast system behavior’s under varied circumstances and spot possible problems before they arise. It is described how these advancements affect PMSM performance, including increased fault tolerance, robustness, and efficiency. The study concludes by highlighting the significance of integrating cutting-edge control and simulation approaches for optimal performance in PMSM systems, as well as important research issues and prospects.